Assessing the risk for opportunism in collective IT investment: A principal-agent based framework for use in inter-firm networks - Christoph Hirnle (Ludwig-Maximilians-Universität München, Institut für Wirtschaftsinformatik und Neue Medien (WIM), 2005)
When managing information technology (IT) infrastructure investments, companies traditionally try to evaluate the monetary costs and benefits of this information system (IS) or seek to implement prudent IT governance structures. However, when collective, cooperation-specific investments in interorganizational information system (IOS) are needed, these classic approaches are flawed as they do not account for central organization-theoretic specifics of investing in cooperation. There is a need for a more comprehensive instrument which includes economic network welfare as perceived individual utility inequalities will keep partners from joining, thereby diminishing network welfare and impeding a successful establishment of the cooperation. The central economic influence on individual utility in collective investments, as identified by Williamson (1985), is the risk for opportunism associated to an investment. The risk for opportunism in collective IT investment is operationalized in three steps: model construction, structured qualitative analysis of relevant investment scenarios with the help of Principal-Agent theory and result aggregation. In the end a novel risk assessment framework is presented. The framework allows any potential IOS participant to quickly read off the risk for opportunism he faces with different IOS alternatives. The discussion shows that purposeful collective IT investments have the following characteristics: every partner actively invests into the IOS, IOS operation is outsourced and, if the IOS is nevertheless sourced from within the cooperation, a decentralized IOS architecture is chosen. A concluding real life case demonstrates the application of the easy-to-use framework.
Keywords: 650; Unternehmensnetzwerk; Betriebliches Informationssystem; Betriebswirtschaftliche Investitionstheorie; Opportunitätskosten; Investitionsrisiko; Neue Institutionenökonomik